STUDENTS' STRATEGIES IN OVERCOMING DIFFICULTIES ENCOUNTERED IN SPEAKING ENGLISH:A Case Study at a Vocational High School in Bandung - Fitria Nurani, - (2012)
The aims of the study are to unveil students' difficulties in speaking English which focus on their linguistic and psychological difficulties. It also aims to investigate their strategies to solve the difficulties. A case study with qualitative approach was employed in this study and it involves 33 second graders of a Vocational High School in Bandung as the respondents. Questionnaire, interview and observation were employed to collect data. The data from questionnaire were analyzed by calculating them while the data from interview were analyzed by reading the transcription, coding and sense making. The difficulties found were classified into difficulties related to speaking competence proposed by Oxford (1990) and difficulties related to psychological trait proposed by Brown (2001) and Harmer (2003). While strategies found were classified into communication strategies outlined by Thornbury (2005) and affective strategy proposed by Oxford (1990). From the study, it was discovered that most students encountered several difficulties in speaking English. It was found that the most excessive difficulties encountered by the students are inadequate grammar competence, lack of vocabulary, and nervousness. Furthermore, to solve the difficulties, the students use various strategies; appealing for help, approximation and affective strategy such as laughing or smiling. From the findings, it can be concluded that insufficient linguistic knowledge may promote some difficulties that can be encountered by the students and the selection of strategy depends on the easiness and accessibility of the strategy. Therefore, the teacher is recommended to provide teaching learning process that offer a lot of opportunities for the students to practise their speaking skill and motivate them to have courage to speak English. Furthermore, the students are suggested to practise their speaking skill as often as they can in order to improve their skill.